Deep‐sequencing of Solanum commersonii small RNA libraries reveals riboregulators involved in cold stress response. (4th February 2019) - Esposito, S.; Aversano, R.; Bradeen, J. M.; Di Matteo, A.; Villano, C.; Carputo, D.
Abstract: Among wild species used in potato breeding, Solanum commersonii displays the highest tolerance to low temperatures under both acclimated (ACC) and non‐acclimated (NACC) conditions. It is also the first wild potato relative with a known whole genome sequence. Recent studies have shown that abiotic stresses induce changes in the expression of many small non‐coding RNA (sncRNA). We determined the small non‐coding RNA (sncRNAome) of two clones of S. commersonii contrasting in their cold response phenotypes via smRNAseq. Differential analysis provided evidence that expression of several miRNAs changed in response to cold stress conditions. Conserved miR408a and miR408b changed their expression under NACC conditions, whereas miR156 and miR169 were differentially expressed only under ACC conditions. We also report changes in tasiRNA and secondary siRNA expression under both stress conditions. Our results reveal possible roles of sncRNA in the regulatory networks associated with tolerance to low temperatures and provide useful information for a more strategic use of genomic resources in potato breeding.